Teaching Outside the Box: A Collaborative Field Experience of Formal and Nonformal Educators - Gross, Lisa; James, J. Joy (Innovations in Science Teacher Education, 2017)
This paper describes a collaborative project in which elementary education (ELED) majors partnered with recreation majors (RM) to develop and implement science lessons in the outdoors. ELED and RM students both need experiential learning to accomplish respective skill sets in multiple settings. The purpose of this project was to provide both undergraduate groups with “real-life” experiences related to their respective fields and in doing so, to promote science learning in natural spaces. ELED and RM students co-constructed inquiry-based lessons and related recreational activities for implementation with 5th grade students. The researchers provide an overview of the project and describe the actions, benefits and outcomes of this university partnership.